Education for Sustainable Development Based of Technological Pedagogical and Content Knowledge using Mixed-Methods Approach in Physics Teaching - Ariska, Melly; Anwar, Yenny; Widodo, Ari; Sari, Diah Kartika; Yusliani, Novi; Rahmannisa, Amanda; Az Zahra, Lutfiah; Milka, Ikbal Adrian; Al Fatih, Zaky (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Sustainable development aims to raise the standard of living for present and future generations. The Sustainable Development Goals (SDGs) are a set of 17 objectives related to sustainable development. Education for Sustainable Development, or ESD, is one initiative to achieve the SDGs. Presenting the findings of literature research on the features and use of ESD in science education is the goal of this paper. The primary source material for this literature study came from seven publications published in different journals. This study utilized a mixed-methods approach with a concurrent triangulation design involving questionnaires, interviews, and FGDs with 78 physics teachers. The TPACK scores showed a mean of 3.10, with the highest score in Attitude (3.27) and the lowest in Inquiry (3.04). The analysis's findings indicate that 1) Eight critical competencies are thought to be crucial for promoting sustainable development. 2) Learning tools, learning media, and learning models are ways ESD can be included in science education. These findings demonstrate that integrating ESD capabilities into science instruction can promote sustainable development and help attain the SDGs. The results highlight the need for targeted training in inquiry-based approaches and technology integration to enhance ESD implementation in physics education.